WTO and India’s Agricultural export Perspectives - J.P.Singh (Journal of Agricultural Extension Management, 2025)
Indian agriculture accounts to a quarter of the country’s GDP and provides employment for approximately 62 per cent of the work force . The food grain output since the 70’s has been on a higher growth over the population growth by way of expansion in area; increase in yields and the market forces as well